The use of social media in developing culinary business in Bandung City - Muhamad Reza Sukmana; Muhammad Wildan Ramadhan; Nugroho Widyanto (PINISI Discretion Review, 2023)
Social media is widely used by the public as a tool to communicate and obtain various information quickly and easily, one of which is for culinary business owners in the city of Bandung, the use of social media has helped many business actors in the culinary field by optimizing the use of social media as a tool to introduce the products they offer, as did one MSME in Bandung named pentol ceker begal, they managed to develop their business only with tiktok social media, this was done because doing marketing through tiktok did not cost money, in contrast to conventional marketing media such as magazines, newspapers, radio, television, which require a large amount of money but the reach is not as wide as using social media. The method used in this study is a qualitative method with data collection techniques using the accidental sampling method. This research is expected to be an inspiration for business people who still use conventional methods to switch to digital methods as promotional media to increase sales.